Kontroversi Pajak atas Transaksi Cryptocurrency di Indonesia - Nur Faizah, Yustin; Wirayudha, Rico Adhitya (Nsc Press, 2025)
The rapid growth of cryptocurrency transactions in Indonesia has raised complex regulatory and fiscal challenges. This study aims to critically examine the taxation policy on cryptocurrency transactions, particularly after the enactment of Minister of Finance Regulation No. 68/PMK.03/2022, which introduces Value Added Tax (VAT) and Income Tax (PPh) on digital asset trading. Using a qualitative descriptive approach and content analysis, the research draws from legal documents, academic literature, and institutional reports to explore the principles, mechanisms, and implications of the policy. Findings indicate that while the policy enhances legal certainty and simplifies tax administration through third-party collection (via registered exchangers), it does not fully comply with the principle of tax fairness. The schedular final tax system imposes obligations without considering taxpayers' ability to pay, potentially undermining equity and increasing the risk of tax avoidance. Additionally, the absence of input tax credit for VAT and challenges in asset valuation due to price volatility further complicate compliance. Despite these issues, cryptocurrency taxation has shown significant fiscal potential, contributing over IDR 285 billion by early 2024. Comparisons with international practices reveal a diverse range of approaches, underscoring the need for a contextual and adaptive domestic framework.In conclusion, while the current regulation represents progress toward capturing digital economy revenue, further refinement is needed to ensure fairness, transparency, and alignment with evolving market conditions. This study contributes to the growing discourse on digital asset taxation and highlights the importance of policy coherence and regulatory preparedness in a rapidly changing financial landscape.